1997
DOI: 10.1111/j.1365-2915.1997.tb00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal distribution of Culicoides imicola in Iberia in relation to the transmission of African horse sickness virus

Abstract: Collections of biting midges were made over 24 months from sixty sites spread across Iberia. Information on the distribution of the vector of African horse sickness virus, Culicoides imicola, from these 3119 samples showed that this species was annually present across south-western Spain as far as 3 degrees 53'W and throughout most of Portugal, up to 41 degrees 5'N. C. imicola was found in all areas where African horse sickness epizootics had occurred in 1987-90 and also in areas outside the epizootic zones. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 10 publications
4
52
0
Order By: Relevance
“…As a direct result of the yearround presence of the vector, these regions are potential enzootic zones for AHS. Rawlings et al (152) have suggested that the northward expansion of C. imicola may be continuing in the Iberian peninsula aided by global climate change. If this is indeed the case, with a projected temperature increase during the early part of the twenty-first century in the order of 1 to 3.5Њ C and bearing in mind that a 1Њ C rise in temperature corresponds to 90 km of latitude and 150 m of altitude, this could extend the distribution of C. imicola and hence the risk of disease, into central Europe.…”
Section: African Horse Sickness Virusmentioning
confidence: 98%
“…As a direct result of the yearround presence of the vector, these regions are potential enzootic zones for AHS. Rawlings et al (152) have suggested that the northward expansion of C. imicola may be continuing in the Iberian peninsula aided by global climate change. If this is indeed the case, with a projected temperature increase during the early part of the twenty-first century in the order of 1 to 3.5Њ C and bearing in mind that a 1Њ C rise in temperature corresponds to 90 km of latitude and 150 m of altitude, this could extend the distribution of C. imicola and hence the risk of disease, into central Europe.…”
Section: African Horse Sickness Virusmentioning
confidence: 98%
“…In southern Africa, Culicoides imicola Kieffer and Culicoides bolitinos Meiswinkel are proven vectors of African horse sickness virus (AHSV) (Venter et al, 1999;Venter et al, 2000;Meiswinkel & Paweska, 2003) and of bluetongue virus (BTV) (Rawlings et al, 1997;Venter et al, 2000;Mellor & Hamblin, 2004). Little is known about the biology and ecology of Culicoides species in West Africa, in particular those involved in the transmission of AHS and BT, which impedes the development of efficient vector control methods.…”
Section: Introductionmentioning
confidence: 98%
“…BTV activity in Europe prior to 2001 was apparently restricted to the known range of C. imicola (Mellor & Pitzolis 1979;Jennings 1983;Mellor et al 1984;Boorman et al 1985;Mellor et al 1985;Boorman 1986;Rawlings et al 1997;Ortega et al 1998). The spread of BTV-9 as far north as Kosovo where C. imicola is absent was therefore a milestone in the epidemiology of BT in Europe, as it represented the first incontrovertible confirmation that field transmission by local northern Palaearctic vector species of Culicoides was possible on a large scale outside the distribution of C. imicola.…”
Section: -2005: Emergence Of Bluetongue Virus In Southern and Easmentioning
confidence: 99%